Composite ion exchange membrane as well as preparation method and application thereof
By introducing a composite structure into the ion exchange membrane of the flow battery, combining low equivalents of cation exchange groups and anion exchange groups, the problem of reducing voltage efficiency in the prior art is solved, and the high energy efficiency of the flow battery is achieved.
Patent Information
- Application Number
- CN202411971511.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
While improving the Coulomb efficiency, the ion exchange membranes in existing flow batteries often reduce voltage efficiency, limiting the improvement of the energy efficiency of the flow batteries.
A composite ion exchange membrane is adopted, which contains both a low equivalent of a substance containing cation exchange group and anion exchange group. By adjusting the molar ratio and distribution of the cation exchange group and anion exchange group, the Coulomb efficiency of the flow battery is greatly improved without reducing the voltage efficiency.
It is achieved while improving the coulomb efficiency of the flow battery, maintaining or improving the voltage efficiency, thereby significantly improving the overall energy efficiency of the flow battery.
Smart Images

Figure CN119812416A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ion exchange membranes and relates to a composite ion exchange membrane and a preparation method and application thereof. Background Art
[0002] As an electrochemical energy storage technology, the working principle of liquid flow battery is to realize the mutual conversion of electrical energy and chemical energy through the redox reaction of active substances in the electrolyte on the electrode. For example, the reaction of the positive electrode of the all-vanadium liquid flow battery during discharge is as follows: VO2 + +2H + +e - →VO 2+ +H2O, the reaction at the negative electrode is as follows: V 2+ →V 3+ +e - It can be seen that vanadium ions convert between different valence states, and the all-vanadium liquid flow battery realizes the conversion between electrical energy and chemical energy.
[0003] The basic structure of a flow battery includes an external electrolyte storage tank, internal electrodes and ion exchange membranes. The function of the ion exchange membrane is to allow specific types of ions to pass through, while blocking the passage of other ions and molecules, and to physically separate the positive and negative electrolytes of the battery. Therefore, the ion exchange membrane, as a key component of a flow battery, is one of the main factors limiting the large-scale commercialization of flow batteries. In flow battery applications, the ion exchange membrane must maintain high efficiency over many cycles, and the performance of the ion exchange membrane greatly affects the energy efficiency of the flow battery.
[0004] However, the commercial cation exchange membrane is a high-equivalent perfluorosulfonic acid proton exchange membrane. The high-equivalent perfluorosulfonic acid ion exchange membrane has low conductivity, which reduces the voltage efficiency of the flow battery. The low-equivalent perfluorosulfonic acid ion exchange membrane has too high ion permeability, which will reduce the coulomb efficiency of the flow battery, thus limiting the improvement of the energy efficiency of the flow battery.
[0005] Although anion exchange membranes have high Coulombic efficiency when used in flow batteries, their electrical conductivity is low, resulting in low voltage efficiency and energy efficiency.
[0006] Based on the above research, there is a need to provide a composite ion exchange membrane that can improve the Coulombic efficiency of the flow battery without reducing the voltage efficiency, thereby improving the overall energy efficiency. Summary of the invention
[0007] The object of the present invention is to provide a composite ion exchange membrane and a preparation method and application thereof. The composite ion exchange membrane includes a substance containing a low equivalent cation exchange group and a substance containing an anion exchange group, which can greatly improve the coulombic efficiency of a liquid flow battery without reducing the voltage efficiency, thereby enabling the liquid flow battery to have a higher energy efficiency.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a composite ion exchange membrane, which includes a substance containing a cation exchange group and a substance containing an anion exchange group.
[0010] Preferably, in the composite ion exchange membrane, the molar ratio of cation exchange groups to anion exchange groups is (5-100):1, preferably (10-50):1.
[0011] Preferably, in the substance containing cation exchange groups, the cation exchange groups include any one of sulfonic acid groups, phosphoric acid groups or carboxylic acid groups, or a combination of at least two of them.
[0012] Preferably, the substance containing cation exchange groups includes any one of perfluorosulfonic acid resin, perfluorocarboxylic acid resin, perfluorophosphoric acid resin, polystyrene sulfonic acid resin, bis[2-(methacryloyloxy)ethyl]phosphate, acrylic resin, sulfonated polyetheretherketone, sulfonated polyaryletherketone or sulfonated polysulfone, or a combination of at least two thereof.
[0013] Preferably, in the substance containing anion exchange groups, the anion exchange groups include any one of piperidinium cations, quininium cations or pyrimidinium cations, or a combination of at least two of them.
[0014] Preferably, the substance containing anion exchange groups includes any one or a combination of at least two of quaternary ammonium salts of aromatic piperidine polymers, aromatic quinine polymers, aromatic pyrimidine polymers, biphenyl-ethyl piperidine copolymers, biphenyl-propyl piperidine copolymers, quaternized biphenyl-piperidine copolymers, quaternized p-terphenyl-piperidine copolymers, p-terphenyl-methyl piperidine copolymers or aromatic quinine polymers.
[0015] Preferably, the composite ion exchange membrane has a thickness of 15 to 100 μm, preferably 25 to 60 μm.
[0016] Preferably, in the composite ion exchange membrane, the substance containing cation exchange groups and the substance containing anion exchange groups are evenly distributed or unevenly distributed.
[0017] Preferably, when the substances containing cation exchange groups and the substances containing anion exchange groups are non-uniformly distributed in the composite ion exchange membrane, the composite ion exchange membrane comprises an anion exchange layer and a cation exchange layer on one side of the anion exchange layer.
[0018] Preferably, when the substances containing cation exchange groups and the substances containing anion exchange groups are non-uniformly distributed in the composite ion exchange membrane, the composite ion exchange membrane comprises a cation exchange layer and anion exchange layers on both sides of the cation exchange layer.
[0019] Preferably, when the substances containing cation exchange groups and the substances containing anion exchange groups are non-uniformly distributed in the composite ion exchange membrane, the composite ion exchange membrane comprises an anion exchange layer and cation exchange layers on both sides of the anion exchange layer.
[0020] Preferably, the cation exchange layer includes the substance containing cation exchange groups, and the anion exchange layer includes the substance containing anion exchange groups.
[0021] In a second aspect, the present invention provides a method for preparing the composite ion exchange membrane as described in the first aspect, the preparation method comprising the following steps:
[0022] The material containing cation exchange groups and the material containing anion exchange groups are mixed and formed into a membrane to obtain the composite ion exchange membrane;
[0023] Alternatively, a substance containing an anion exchange group is first formed into a membrane to obtain an anion exchange layer, and then a substance containing a cation exchange group is formed into a membrane on one surface of the anion exchange layer to obtain the composite ion exchange membrane;
[0024] Alternatively, a substance containing cation exchange groups is first formed into a membrane to obtain a cation exchange layer, and then a substance containing anion exchange groups is formed into a membrane on one surface of the cation exchange layer to obtain the composite ion exchange membrane;
[0025] Alternatively, a substance containing an anion exchange group is first formed into a membrane to obtain an anion exchange layer, and then a substance containing a cation exchange group is formed into a membrane on one side of the anion exchange layer to obtain a cation exchange layer, and finally a substance containing an anion exchange group is formed into a membrane on the surface of the cation exchange layer to obtain the composite ion exchange membrane;
[0026] Alternatively, a substance containing cation exchange groups is first formed into a membrane to obtain a cation exchange layer, and then a substance containing anion exchange groups is formed into a membrane on one surface of the cation exchange layer to obtain an anion exchange layer, and finally a substance containing cation exchange groups is formed into a membrane on the surface of the anion exchange layer to obtain the composite ion exchange membrane.
[0027] Preferably, the film-forming method includes a solution casting method or a melt extrusion method.
[0028] In a third aspect, the present invention provides a liquid flow battery, comprising the composite ion exchange membrane as described in the first aspect.
[0029] Preferably, the type of the liquid flow battery includes any one of an acidic liquid flow battery system, a neutral liquid flow battery or an alkaline liquid flow battery.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention makes the composite ion exchange membrane include both the substance containing cation exchange groups and the substance containing anion exchange groups. Since the anion exchange group is positively charged, according to the principle of like charges holding each other, the passage of cations such as vanadium ions can be reduced, while the coulomb efficiency of the liquid flow battery is greatly improved without reducing the voltage efficiency, so that the liquid flow battery can have higher energy efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a schematic diagram of the structure of the composite ion exchange membrane described in Example 1 in a specific implementation manner of the present invention;
[0033] Figure 2 This is a schematic diagram of the structure of the composite ion exchange membrane described in Example 3 in a specific implementation manner of the present invention;
[0034] Figure 3 This is a schematic diagram of the structure of the composite ion exchange membrane described in Example 4 in a specific implementation manner of the present invention;
[0035] Among them, 1-anion exchange layer, 2-cation exchange layer. DETAILED DESCRIPTION
[0036] The technical solution of the present invention is further described below by means of specific implementation methods. It should be understood by those skilled in the art that the specific implementation methods are only used to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0037] In a first aspect, a specific embodiment of the present invention provides a composite ion exchange membrane, wherein the composite ion exchange membrane includes a substance containing a cation exchange group and a substance containing an anion exchange group.
[0038] According to the working principle of liquid flow battery, ion exchange membrane needs to allow protons to pass through to form a circulating loop. At the same time, ion exchange membrane acts as an ion barrier, and cations of different valences on both sides of the liquid flow battery cannot pass through. For example, in the all-vanadium liquid flow battery, ion exchange membrane cannot allow vanadium of different valences to pass through, but protons and vanadium ions are all cations. If only cation exchange membrane is used, while protons pass through the cation exchange membrane, cations of other valences such as vanadium ions will also pass through a certain amount, which will reduce the coulomb efficiency of the liquid flow battery. Only anion exchange membrane is used, although it can hinder the passage of cations of other valences such as vanadium ions, it also increases the difficulty of protons passing through, thereby reducing the voltage efficiency of the battery. When the composite ion exchange membrane of the present invention includes a substance containing a cation exchange group, it also includes a substance containing an anion exchange group, so that the composite ion exchange membrane includes both cation exchange groups and anion exchange groups. Since the anion exchange group is positively charged, according to the principle of like-charge holding, it can reduce the passage of cations such as vanadium ions, thereby effectively ensuring the coulomb efficiency of the liquid flow battery without reducing the voltage efficiency.
[0039] The composite ion exchange membrane of the present invention includes both a substance containing a cation exchange group and a substance containing an anion exchange group. The cation exchange group and the anion exchange group are not in the same substance, for example, they are not on the same polymer chain. Since the preparation of the substance containing both the cation exchange group and the anion exchange group is difficult and costly, and the amount of the anion and cation exchange groups is not easy to control, the present invention directly uses the substance containing the cation exchange group and the substance containing the anion exchange group in the same ion exchange membrane, which greatly reduces the preparation difficulty and cost of the composite ion exchange membrane and makes it easy to control the content of the anion and cation exchange groups in the composite ion exchange membrane.
[0040] In some embodiments, in the composite ion exchange membrane, the molar ratio of cation exchange groups to anion exchange groups is (5-100):1, for example, it can be 5:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 80:1, 90:1 or 100:1, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable, preferably (10-50):1.
[0041] In order to ensure that protons pass through the composite ion exchange membrane in sufficient quantity and smoothly, the composite ion exchange membrane of the present invention uses relatively more substances containing cation exchange groups. Therefore, it is preferred that the cation exchange groups and anion exchange groups are within the above-mentioned ratio range, which can not only ensure the passage of protons, but also reduce the passage of other cations such as vanadium ions. It can greatly improve the coulombic efficiency of the liquid flow battery without reducing the voltage efficiency, thereby enabling the liquid flow battery to have higher energy efficiency.
[0042] In some embodiments, in the substance containing cation exchange groups, the cation exchange groups include any one of sulfonic acid groups, phosphoric acid groups or carboxylic acid groups, or a combination of at least two of them.
[0043] In some embodiments, the substance containing a cation exchange group includes any one of perfluorosulfonic acid resin, perfluorocarboxylic acid resin, perfluorophosphoric acid resin, polystyrene sulfonic acid resin, bis[2-(methacryloyloxy)ethyl]phosphate, sulfonated polyetheretherketone, sulfonated polyaryletherketone or sulfonated polysulfone, or a combination of at least two thereof.
[0044] In some embodiments, the equivalent EW value of the material containing cation exchange groups is below 1100, for example, 1100, 1000, 900, 800 or 700, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] In some embodiments, in the substance containing anion exchange groups, the anion exchange groups include any one of piperidinium cations, quininium cations, or pyrimidinium cations, or a combination of at least two thereof.
[0046] In some embodiments, the substance containing anion exchange groups includes any one of an aromatic piperidine polymer, an aromatic quinine polymer, an aromatic pyrimidine polymer, a biphenyl-ethyl piperidine copolymer, a biphenyl-propyl piperidine copolymer, a quaternized biphenyl-piperidine copolymer, a quaternized p-terphenyl-piperidine copolymer, a p-terphenyl-methyl piperidine copolymer or a polyaryl quinine polymer, or a combination of at least two thereof.
[0047] In some embodiments, the thickness of the composite ion exchange membrane is 15 to 100 μm, for example, 15 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm, but is not limited to the listed values. Other unlisted values within the numerical range are also applicable, preferably 25 to 60 μm.
[0048] In some embodiments, in the composite ion exchange membrane, the substance containing cation exchange groups and the substance containing anion exchange groups are evenly distributed or unevenly distributed.
[0049] In the composite ion exchange membrane of the present invention, the substance containing cation exchange groups and the substance containing anion exchange groups can be evenly distributed or non-evenly distributed, as long as they contain cation exchange groups and anion exchange groups.
[0050] In some embodiments, when the substances containing cation exchange groups and the substances containing anion exchange groups are non-uniformly distributed in the composite ion exchange membrane, the composite ion exchange membrane includes an anion exchange layer and a cation exchange layer on one side of the anion exchange layer.
[0051] When the composite ion exchange membrane of the present invention has a structure of stacked anion exchange layers and cation exchange layers, when the composite ion exchange membrane is used in a flow battery, the anion exchange layer faces the negative electrode and the cation exchange layer faces the positive electrode.
[0052] In some embodiments, when the substances containing cation exchange groups and the substances containing anion exchange groups are unevenly distributed in the composite ion exchange membrane, the composite ion exchange membrane includes a cation exchange layer and anion exchange layers on both sides of the cation exchange layer. At this time, the thickness of the anion exchange layers on both sides of the cation exchange layer can be the same or different.
[0053] In some embodiments, when the substances containing cation exchange groups and the substances containing anion exchange groups are unevenly distributed in the composite ion exchange membrane, the composite ion exchange membrane includes an anion exchange layer and a cation exchange layer on both sides of the anion exchange layer. At this time, the thickness of the cation exchange layer on both sides of the anion exchange layer can be the same or different.
[0054] When the substances containing cation exchange groups and substances containing anion exchange groups are unevenly distributed in the composite ion exchange membrane, from the perspective of preparation technology, the composite ion exchange membrane of the present invention preferably includes a cation exchange layer and an anion exchange layer on one side of the cation exchange layer.
[0055] In some embodiments, the cation exchange layer includes the substance containing cation exchange groups, and the anion exchange layer includes the substance containing anion exchange groups.
[0056] In a second aspect, a specific embodiment of the present invention provides a method for preparing the composite ion exchange membrane of the first aspect, the preparation method comprising the following steps:
[0057] The material containing cation exchange groups and the material containing anion exchange groups are mixed and formed into a membrane to obtain the composite ion exchange membrane;
[0058] Alternatively, a substance containing an anion exchange group is first formed into a membrane to obtain an anion exchange layer, and then a substance containing a cation exchange group is formed into a membrane on one surface of the anion exchange layer to obtain the composite ion exchange membrane;
[0059] Alternatively, a substance containing cation exchange groups is first formed into a membrane to obtain a cation exchange layer, and then a substance containing anion exchange groups is formed into a membrane on one surface of the cation exchange layer to obtain the composite ion exchange membrane;
[0060] Alternatively, a substance containing an anion exchange group is first formed into a membrane to obtain an anion exchange layer, and then a substance containing a cation exchange group is formed into a membrane on one side of the anion exchange layer to obtain a cation exchange layer, and finally a substance containing an anion exchange group is formed into a membrane on the surface of the cation exchange layer to obtain the composite ion exchange membrane;
[0061] Alternatively, a substance containing cation exchange groups is first formed into a membrane to obtain a cation exchange layer, and then a substance containing anion exchange groups is formed into a membrane on one surface of the cation exchange layer to obtain an anion exchange layer, and finally a substance containing cation exchange groups is formed into a membrane on the surface of the anion exchange layer to obtain the composite ion exchange membrane.
[0062] When the material containing cation exchange groups and the material containing anion exchange groups are uniformly distributed in the composite ion exchange membrane of the present invention, the composite ion exchange membrane is prepared by mixing and forming the material containing cation exchange groups and the material containing anion exchange groups.
[0063] When the substances containing cation exchange groups and the substances containing anion exchange groups are unevenly distributed in the composite ion exchange membrane of the present invention, the membrane is first prepared by using the substances containing cation exchange groups or the substances containing anion exchange groups, and then the membrane is further prepared according to the structure of the composite ion exchange membrane.
[0064] In some embodiments, the film forming method includes solution casting or melt extrusion.
[0065] In some embodiments, in the composite ion exchange membrane of the present invention, when the substance containing cation exchange groups and the substance containing anion exchange groups are non-uniformly distributed, the membrane is prepared by solution casting.
[0066] Illustratively, when the substance containing cation exchange groups and the substance containing anion exchange groups are unevenly distributed, the preparation method includes: first casting the substance containing cation exchange groups, drying or semi-drying to obtain a cation exchange layer, and then casting the substance containing anion exchange groups on the surface of one side of the cation exchange layer to obtain the composite ion exchange membrane.
[0067] In a third aspect, a specific embodiment of the present invention provides a liquid flow battery, wherein the liquid flow battery comprises the composite ion exchange membrane as described in the first aspect.
[0068] In some embodiments, the type of flow battery includes any one of an acidic flow battery system (such as an all-vanadium flow battery, an iron-chromium flow battery), a neutral flow battery (such as an organic flow battery, a neutral iron-chromium flow battery) or an alkaline flow battery (such as an alkaline zinc-iron flow battery, an all-iron flow battery).
[0069] The technical solution of the present invention is further illustrated by specific embodiments below.
[0070] Example 1
[0071] This embodiment provides a composite ion exchange membrane and a preparation method thereof, wherein the composite ion exchange membrane is Figure 1 As shown, it includes an anion exchange layer 1 and a cation exchange layer 2 on one side of the anion exchange layer 1, wherein the cation exchange layer 2 includes a substance containing a cation exchange group, and the anion exchange layer 1 includes a substance containing an anion exchange group;
[0072] The substance containing cation exchange groups is a perfluorosulfonic acid resin with an equivalent weight (EW) value of 900, and the substance containing anion exchange groups is a quaternized arylquinine polymer;
[0073] In the composite ion exchange membrane, the molar ratio of cation exchange groups to anion exchange groups is 16:1;
[0074] The total thickness of the composite ion exchange membrane is 50 μm, the thickness of the cation exchange layer 2 is 47 μm, and the thickness of the anion exchange layer 1 is 3 μm;
[0075] The preparation method of the composite ion exchange membrane comprises the following steps:
[0076] A perfluorosulfonic acid resin solution with an equivalent EW value of 900 is cast, and after drying, a cation exchange layer is obtained. A substance containing an anion exchange group is secondarily cast on the surface of the cation exchange layer, and after drying, the composite ion exchange membrane is obtained.
[0077] Example 2
[0078] The present embodiment provides a composite ion exchange membrane and a preparation method thereof, wherein the composite ion exchange membrane comprises an anion exchange layer and a cation exchange layer on one side of the anion exchange layer, wherein the cation exchange layer comprises a substance containing a cation exchange group, and the anion exchange layer comprises a substance containing an anion exchange group;
[0079] The substance containing cation exchange groups is a perfluorosulfonic acid resin with an equivalent weight (EW) value of 900, and the substance containing anion exchange groups is a quaternized arylquinine polymer;
[0080] In the composite ion exchange membrane, the molar ratio of cation exchange groups to anion exchange groups is 10:1;
[0081] The total thickness of the composite ion exchange membrane is 35 μm, the thickness of the cation exchange layer is 32 μm, and the thickness of the anion exchange layer is 3 μm;
[0082] The preparation method of the composite ion exchange membrane comprises the following steps:
[0083] A perfluorosulfonic acid resin solution with an equivalent EW value of 900 is cast, and after drying, a cation exchange layer is obtained. A substance containing an anion exchange group is secondarily cast on the surface of the cation exchange layer, and after drying, the composite ion exchange membrane is obtained.
[0084] Example 3
[0085] This embodiment provides a composite ion exchange membrane and a preparation method thereof, wherein the composite ion exchange membrane is Figure 2 As shown, it includes a cation exchange layer 2 and an anion exchange layer 1 on both sides of the cation exchange layer 2, wherein the cation exchange layer 2 includes a substance containing a cation exchange group, and the anion exchange layer 1 includes a substance containing an anion exchange group;
[0086] The substance containing cation exchange groups is a perfluorosulfonic acid resin with an equivalent weight (EW) value of 900, and the substance containing anion exchange groups is a quaternized arylquinine polymer;
[0087] In the composite ion exchange membrane, the molar ratio of cation exchange groups to anion exchange groups is 16:1;
[0088] The total thickness of the composite ion exchange membrane is 50 μm, the thickness of the cation exchange layer 2 is 47 μm, and the thickness of the anion exchange layer 1 is 1.5 μm;
[0089] The preparation method of the composite ion exchange membrane comprises the following steps:
[0090] First, a material solution containing anion exchange groups is cast to obtain an anion exchange layer. After drying, a material solution containing cation exchange groups is cast on one side of the anion exchange layer to obtain a cation exchange layer. After drying, a material solution containing anion exchange groups is cast on the surface of the cation exchange layer again to obtain the composite ion exchange membrane.
[0091] Example 4
[0092] This embodiment provides a composite ion exchange membrane and a preparation method thereof, wherein the composite ion exchange membrane is Figure 3 As shown, it includes an anion exchange layer 1 and cation exchange layers 2 on both sides of the anion exchange layer 1, wherein the cation exchange layer 2 includes a substance containing a cation exchange group, and the anion exchange layer 1 includes a substance containing anion exchange groups;
[0093] The substance containing cation exchange groups is a perfluorosulfonic acid resin with an equivalent weight (EW) value of 900, and the substance containing anion exchange groups is a polyarylquinine polymer;
[0094] In the composite ion exchange membrane, the molar ratio of cation exchange groups to anion exchange groups is 16:1;
[0095] The total thickness of the composite ion exchange membrane is 50 μm, the thickness of the cation exchange layer 2 is 23.5 μm, and the thickness of the anion exchange layer 1 is 3 μm;
[0096] The preparation method of the composite ion exchange membrane comprises the following steps:
[0097] First, a material solution containing cation exchange groups is cast to obtain a cation exchange layer. After drying, a material solution containing anion exchange groups is cast on one side of the cation exchange layer to obtain an anion exchange layer. After drying, a material solution containing cation exchange groups is cast on the surface of the anion exchange layer again to obtain the composite ion exchange membrane.
[0098] Example 5
[0099] This embodiment provides a composite ion exchange membrane and a preparation method thereof, wherein the composite ion exchange membrane includes a substance containing a cation exchange group and a substance containing an anion exchange group;
[0100] The substance containing cation exchange groups is a perfluorosulfonic acid resin with an equivalent weight (EW) value of 900, and the substance containing anion exchange groups is a quaternized arylquinine polymer;
[0101] In the composite ion exchange membrane, the molar ratio of cation exchange groups to anion exchange groups is 16:1;
[0102] The total thickness of the composite ion exchange membrane is 50 μm;
[0103] The preparation method of the composite ion exchange membrane comprises the following steps:
[0104] The perfluorosulfonic acid resin solution with an equivalent EW value of 900 and the quaternized arylquinine polymer solution are mixed, and after uniform mixing, the mixture is cast, and after drying, the composite ion exchange membrane is obtained.
[0105] Example 6
[0106] This embodiment provides a composite ion exchange membrane and a preparation method thereof. The composite ion exchange membrane is the same as that of Embodiment 1 except that the molar ratio of cation exchange groups to anion exchange groups is 5:1 and the thickness of the cation exchange layer and the anion exchange layer are adaptable.
[0107] Example 7
[0108] This embodiment provides a composite ion exchange membrane and a preparation method thereof. The composite ion exchange membrane is the same as that of Embodiment 1 except that the molar ratio of cation exchange groups to anion exchange groups is 50:1 and the thickness of the cation exchange layer and the anion exchange layer are adaptable.
[0109] Example 8
[0110] This embodiment provides a composite ion exchange membrane and a preparation process thereof. The composite ion exchange membrane is the same as that of Embodiment 1 except that the EW value of the perfluorosulfonic acid resin is 750.
[0111] Example 9
[0112] This embodiment provides a composite ion exchange membrane and a preparation method thereof. The composite ion exchange membrane is the same as that of Embodiment 1 except that the substance containing anion exchange groups is a quaternized arylpiperidine polymer.
[0113] Example 10
[0114] This embodiment provides a composite ion exchange membrane and a preparation method thereof. The composite ion exchange membrane is the same as that of Embodiment 1 except that the substance containing the cation exchange group is sulfonated polyetheretherketone with an EW value of 650.
[0115] Embodiment 11
[0116] This embodiment provides a composite ion exchange membrane and a preparation method thereof. The preparation method of the composite ion exchange membrane is the same as that of Embodiment 1 except that the solution casting process is replaced by a process of spraying a solution of a substance containing anion exchange groups when preparing the anion layer.
[0117] Example 12
[0118] This embodiment provides a composite ion exchange membrane and a preparation method thereof. The preparation method of the composite ion exchange membrane is the same as that of Embodiment 5 except that the solution casting process is replaced by a melt extrusion process.
[0119] Comparative Example 1
[0120] This comparative example provides an ion exchange membrane, the ion exchange membrane comprises a perfluorosulfonic acid resin having an equivalent EW value of 900, and the thickness of the ion exchange membrane is 50 μm;
[0121] The method for preparing the ion exchange membrane comprises the following steps:
[0122] The ion exchange membrane is obtained by casting a perfluorosulfonic acid resin solution with an equivalent EW value of 900 and drying it.
[0123] Comparative Example 2
[0124] This comparative example provides an ion exchange membrane, the ion exchange membrane comprises a perfluorosulfonic acid resin having an equivalent EW value of 900, and the thickness of the ion exchange membrane is 35 μm;
[0125] The method for preparing the ion exchange membrane comprises the following steps:
[0126] The ion exchange membrane is obtained by casting a perfluorosulfonic acid resin solution with an equivalent EW value of 900 and drying it.
[0127] Comparative Example 3
[0128] This comparative example provides an ion exchange membrane, the ion exchange membrane comprises a substance containing anion exchange groups, the substance containing anion exchange groups is a quaternized arylquinine polymer, and the thickness of the ion exchange membrane is 50 μm;
[0129] The method for preparing the ion exchange membrane comprises the following steps:
[0130] The quaternized arylquinine polymer solution is cast and dried to obtain the anion exchange membrane.
[0131] The ion exchange membranes of the above embodiments and comparative examples were applied to the all-vanadium redox flow battery test, wherein when the ion exchange membrane was a stacked anion exchange layer and a cation exchange layer structure, Figure 1 Structure, the anion exchange layer faces the negative electrode of the all-vanadium redox flow battery, and the cation exchange layer faces the positive electrode of the all-vanadium redox flow battery; Figure 2 and Figure 3 The structure and the anion and cation exchange groups are evenly distributed without distinguishing between positive and negative electrodes; the positive electrode of the all-vanadium battery is VO 2+ / VO2 + , the negative pole is V 2+ / V 3+ The electrolyte is a vanadyl sulfate solution; the all-vanadium battery is at an electrolyte temperature of 50°C and a current density of 200 mA / cm 2 The results of the test under the following conditions are shown in Table 1:
[0132] Table 1
[0133] CE(%) VE(%) EE(%) Example 1 98.83 85.13 84.13 Example 2 98.11 87.57 85.92 Example 3 98.21 85.24 83.71 Example 4 98.50 85.30 84.02 Example 5 97.94 84.22 82.48 Example 6 99.12 83.26 82.55 Example 7 97.83 85.55 83.69 Example 8 97.59 86.61 84.52 Example 9 97.68 85.87 83.88 Example 10 98.15 84.92 83.35 Embodiment 11 98.43 85.62 84.28 Example 12 97.78 84.26 82.39 Comparative Example 1 95.24 84.24 80.23 Comparative Example 2 93.50 86.30 80.69 Comparative Example 3 99.23 74.92 74.34
[0134] In Table 1, CE refers to coulombic efficiency, VE refers to voltage efficiency, and EE refers to energy efficiency.
[0135] From Table 1 we can see that:
[0136] (1) By comparing Example 1 with Comparative Example 1, it can be seen that the coulombic efficiency of Example 1 is improved by 3.59% and the energy efficiency is improved by 3.90% compared with Comparative Example 1, and the voltage efficiency does not decrease. By comparing Example 2 with Comparative Example 2, it can be seen that the coulombic efficiency of Example 2 is improved by 4.61% and the energy efficiency is improved by 5.23% compared with Comparative Example 2, and the voltage efficiency does not decrease. This shows that the composite ion exchange membrane of the present invention can significantly improve the coulombic efficiency while maintaining high voltage efficiency compared with the currently commercially available perfluorosulfonic acid type cation exchange membrane, so that the energy efficiency is greatly improved.
[0137] (2) It can be seen from Example 1 and Comparative Example 3 that the composite ion exchange membrane of the present invention has a voltage efficiency increased by 10.21% compared to the anion exchange membrane, and thus the energy efficiency is also greatly increased by 9.79%.
[0138] (4) It can be seen from Examples 1-5 that in the composite ion exchange membrane of the present invention, the substance containing cation exchange groups and the substance containing anion exchange groups can be uniformly distributed or non-uniformly distributed. Considering the difficulty of the preparation process, the preparation process of Examples 1 and 2 is easier than that of Examples 3-5.
[0139] (5) It can be seen from Example 1 and Examples 6-7 that in the composite ion exchange membrane of the present invention, the molar ratio of cation exchange groups to anion exchange groups is preferably (10-50):1; it can be seen from Examples 1 and Examples 8-10 that the cation exchange groups of the present invention include sulfonic acid groups, phosphoric acid groups or carboxylic acid groups, and the anion exchange groups include piperidinium cations, quinine cations or pyrimidinium cations; it can be seen from Examples 1 and Examples 11-12 that in the preparation method of the composite ion exchange membrane of the present invention, the solution casting process can be replaced by a spraying and melt extrusion process.
[0140] In summary, the present invention provides a composite ion exchange membrane and a preparation method and application thereof. The composite ion exchange membrane includes a substance containing a cation exchange group and a substance containing an anion exchange group, which can greatly improve the coulombic efficiency of the liquid flow battery without reducing the voltage efficiency, thereby enabling the liquid flow battery to have higher energy efficiency.
[0141] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A composite ion exchange membrane, characterized in that: The composite ion exchange membrane comprises a substance containing a cation exchange group and a substance containing an anion exchange group.
2. The composite ion exchange membrane according to claim 1, characterized in that: In the composite ion exchange membrane, the molar ratio of cation exchange groups to anion exchange groups is (5-100):1, preferably (10-50):
1.
3. The composite ion exchange membrane according to claim 1 or 2, characterized in that: In the substance containing cation exchange groups, the cation exchange groups include any one of sulfonic acid groups, phosphoric acid groups or carboxylic acid groups, or a combination of at least two of them; Preferably, the substance containing cation exchange groups includes any one of perfluorosulfonic acid resin, perfluorocarboxylic acid resin, perfluorophosphoric acid resin, polystyrene sulfonic acid resin, bis[2-(methacryloyloxy)ethyl]phosphate, acrylic resin, sulfonated polyetheretherketone, sulfonated polyaryletherketone or sulfonated polysulfone, or a combination of at least two thereof.
4. The composite ion exchange membrane according to claim 1 or 2, characterized in that: In the substance containing anion exchange groups, the anion exchange groups include any one of piperidinium cations, quininium cations or pyrimidinium cations or a combination of at least two thereof; Preferably, the substance containing anion exchange groups includes any one or a combination of at least two of an aryl piperidine polymer, an aryl quinine polymer, an aryl pyrimidine polymer, a biphenyl-ethyl piperidine copolymer, a biphenyl-propyl piperidine copolymer, a quaternized biphenyl-piperidine copolymer, a quaternized p-terphenyl-piperidine copolymer, a p-terphenyl-methyl piperidine copolymer or a polyaryl quinine polymer.
5. The composite ion exchange membrane according to claim 1 or 2, characterized in that: The thickness of the composite ion exchange membrane is 15 to 100 μm, preferably 25 to 60 μm; Preferably, in the composite ion exchange membrane, the substance containing cation exchange groups and the substance containing anion exchange groups are evenly distributed or unevenly distributed.
6. The composite ion exchange membrane according to claim 5, characterized in that: When the substance containing cation exchange groups and the substance containing anion exchange groups are non-uniformly distributed in the composite ion exchange membrane, the composite ion exchange membrane comprises an anion exchange layer and a cation exchange layer on one side of the anion exchange layer; Preferably, in the composite ion exchange membrane, when the substance containing cation exchange groups and the substance containing anion exchange groups are non-uniformly distributed, the composite ion exchange membrane comprises a cation exchange layer and anion exchange layers on both sides of the cation exchange layer; Preferably, in the composite ion exchange membrane, when the substance containing cation exchange groups and the substance containing anion exchange groups are non-uniformly distributed, the composite ion exchange membrane comprises an anion exchange layer and cation exchange layers on both sides of the anion exchange layer; Preferably, the cation exchange layer includes the substance containing cation exchange groups, and the anion exchange layer includes the substance containing anion exchange groups.
7. A method for preparing a composite ion exchange membrane according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: The material containing cation exchange groups and the material containing anion exchange groups are mixed and formed into a membrane to obtain the composite ion exchange membrane; Alternatively, a substance containing an anion exchange group is first formed into a membrane to obtain an anion exchange layer, and then a substance containing a cation exchange group is formed into a membrane on one surface of the anion exchange layer to obtain the composite ion exchange membrane; Alternatively, a substance containing cation exchange groups is first formed into a membrane to obtain a cation exchange layer, and then a substance containing anion exchange groups is formed into a membrane on one surface of the cation exchange layer to obtain the composite ion exchange membrane; Alternatively, a substance containing an anion exchange group is first formed into a membrane to obtain an anion exchange layer, and then a substance containing a cation exchange group is formed into a membrane on one side of the anion exchange layer to obtain a cation exchange layer, and finally a substance containing an anion exchange group is formed into a membrane on the surface of the cation exchange layer to obtain the composite ion exchange membrane; Alternatively, a substance containing cation exchange groups is first formed into a membrane to obtain a cation exchange layer, and then a substance containing anion exchange groups is formed into a membrane on one surface of the cation exchange layer to obtain an anion exchange layer, and finally a substance containing cation exchange groups is formed into a membrane on the surface of the anion exchange layer to obtain the composite ion exchange membrane.
8. The preparation method according to claim 7, characterized in that: The film-forming method includes a solution casting method or a melt extrusion method.
9. A liquid flow battery, characterized in that: The liquid flow battery comprises the composite ion exchange membrane according to any one of claims 1 to 6.
10. The liquid flow battery according to claim 9, characterized in that: The type of the flow battery includes any one of an acidic flow battery system, a neutral flow battery or an alkaline flow battery.
Citation Information
Patent Citations
Ionic crosslinking type amphoteric ion exchange membrane, preparation method and application of ionic crosslinking type amphoteric ion exchange membrane in selective electrodialysis
CN114405286A
Bipolar membrane containing MOF (Metal Organic Framework) catalyst middle layer as well as preparation method and application of bipolar membrane
CN118286869A
Preparation method of monolithic bipolar membrane based on polyarylether sulfone
CN119016118A
Bipolar film and its preparing process
CN1250681A
Production of bipolar membrane
JP1994032918A